Ciclo do Petróleo e Desenvolvimento Socioeconômico no Município de Campos dos Goytacazes – 1999/2014 - José Eduardo Manhães da Silva (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
Campos dos Goytacazes, county located in the north region of the state of Rio de Janeiro, until recently, has been the greatest receiver of royalties and special participations in the country. The objective of this article is to observe the contribution of the expansive cycle of the oil industry in the Campos Basin, in order to overcome local underdevelopment and to promote the socioeconomic development. The methodology analize the socioeconomic indicators of Campos dos Goytacazes in the period 1999/2014, compared to the municipalities Macaé and Niterói, and complemented this analize by research in the scientific literature about the subject. Concludes that, in despite the virtuous cycle of oil and the generous revenues from royalties and special participations shown by the county, it’s observed that underdevelopment not only persists, but also increases due to institutional deterioration.